Analysis of Facilities and Infrastructure Policy Management and Its Implications for Educational Institutions : (Case Study at SDIT Bina Lestari, Bekasi Regency) - Luthfi Yasykur Luthfi; Juliani Jamilah; Khusni; Qiqi Yuliati Zaqiah (EDUTEC : Journal of Education And Technology, 2024)
This study aims to analyze the management of facilities and infrastructure at SDIT Bina Lestari in Bekasi Regency, aligning with the minimum standards set by Permendiknas and Permendikbudristek. Using a qualitative case study approach, data were collected through observations, interviews with the principal and the facilities management team, and documentation review. Primary and secondary data sources were utilized. Data analysis followed the Miles and Huberman model, involving data reduction, data presentation, and conclusion drawing. The findings indicate that: (1) Planning for facilities and infrastructure at SDIT Bina Lestari is systematically conducted, with items being proposed, reviewed by the principal, and discussed annually with the school committee and the Foundation. (2) Procurement of facilities and infrastructure involves purchases, grants, and reconditioning. (3) The arrangement of facilities and infrastructure is efficiently managed to support effective and conducive learning environments. (4) The inventory of facilities and infrastructure is meticulously recorded annually to monitor the condition and replacement needs of items.